Information and communication technology application's usage in hotel industry / Azdel Abdul Aziz... [et al.] - Abdul Aziz, Azdel; Saiful Bakhtiar, Mohd Faeez; Kamaruddin, Mohd Syaquif Yasin; Ahmad, Noor Azmi (UiTM Press, 2012)
Hotel's information and communication technology (ICT) has affected society and its surroundings in many ways. Most of hotels in this world use ICT as to ease their tasks such as taking reservation, room management, telecommunication, and guest accounting. In Malaysia, hotels have started to use ICT application as an important strategic asset. ICT has been rapidly changed or enhanced from time to time and many hotels invest a lot of money to ensure that they have the latest technology. By using quantitative approach, this paper analyzed the levels of usage of ICT applications used in Room Division and Food and Beverage Department of hotels. Through self-administered questionnaires, 350 respondents from 28 five stars hotels in Kuala Lumpur were approach using random stratified sampling. It is appear that room division department has the highest level of ICT usage. This outcome had significant implication to the hotel operators on how to prioritize the importance of the hotel's ICT application.